A blood biomarker and clinical correlation cohort study protocol to diagnose sports-related concussion and monitor recovery in elite rugby - Kearns, J.; Ross, A. M.; Walsh, D. R.; Cahalane, R. M.; Hinchion, R.; Ryan, M. C.; Conway, E.; Comyns, T. M.; Kenny, I. C.; O`Connor, E. M.; McGourty, K. D. (BMJ Open Sport & Exercise Medicine, 2020)
Introduction In professional rugby, sports-related concussion (SRC) remains the most frequent time loss injury. Therefore, accurately diagnosing SRC and monitoring player recovery, through a multi-modal assessment process, is critical to SRC management. In this protocol study, we aim to assess SRC over multiple time points post-injury to determine the value of multi-modal assessments to monitor player recovery. This is of significance to minimise premature return-to-play and, ultimately, to reduce the long-term effects associated with SRC. The study will also establish the logistics of implementing such a study in a professional setting to monitor a player`s SRC recovery.